2021
DOI: 10.3390/ani11051365
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Upregulates the Expression of the TGF-β Receptors ALK5 and BMPR2 during the Gonadal Development of Schizothorax prenanti

Abstract: TGF-β receptors play important roles in mediating TGF-β signals during gonadal development. To identify the functions of TGF-β receptors, including the type I receptor (activin receptor-like kinase 5, ALK5) and type II receptor (bone morphogenetic protein receptor 2, BMPR2), during the gonadal development of S. prenanti, the full-length cDNA sequences of ALK5 and BMPR2 were isolated and characterized. Their expression patterns in developing gonads and in the gonads of exogenous estradiol (E2) -fed fish were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Despite the sequence divergence, the results showed that the ligand binding domain (ActRI/ActRII domain) and kinase domain of M. albus sequence were highly conserved with other animals, including species such as Homo sapiens, Gallus, M. salmoides and S. argus . The ActRI/ActRII domain and kinase domain play a crucial role in ligand recognition and activation, similar to the results surveyed in Anguilla australis [ 25 ] and S. prenanti [ 15 ]. The results of the phylogenetic tree and Bmpr2 sequence structure characteristics showed that ricefield eel type II Bmp receptor had higher similarity with Bmpr2 of bony fishes, especially with Bmpr2b.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Despite the sequence divergence, the results showed that the ligand binding domain (ActRI/ActRII domain) and kinase domain of M. albus sequence were highly conserved with other animals, including species such as Homo sapiens, Gallus, M. salmoides and S. argus . The ActRI/ActRII domain and kinase domain play a crucial role in ligand recognition and activation, similar to the results surveyed in Anguilla australis [ 25 ] and S. prenanti [ 15 ]. The results of the phylogenetic tree and Bmpr2 sequence structure characteristics showed that ricefield eel type II Bmp receptor had higher similarity with Bmpr2 of bony fishes, especially with Bmpr2b.…”
Section: Discussionsupporting
confidence: 85%
“…In zebrafish, bmpr2a and bmpr2b mRNA expression occurs mainly in the gill and testis [ 16 ]. In this paper, we found that the tissue expression patterns of bmpr2 mRNA in ricefield eels were markedly higher in the ovary than in other tissues, consistent with those of bmpr2 in S. prenanti [ 15 ].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…DHEA decreased the expression of β-catenin, resulting in upregulation of MMP13 and downregulation of TIMP1 and COL2A1 [ 131 ]. TGF-β signaling pathway ( B ): E2 upregulates the expression of ALK5 receptors, promoting ACAN and COL2A1 production and inhibiting COL10A1 , MMP13 , VEGF , OPN , BGLAP , and ALP expression [ 9 , 135 , 136 ]. Cellular energy and survival related pathways ( C ): PI3K/AKT signaling pathway is downregulated in human cartilage tissues with OA or in OA-like chondrocytes exposed to IL1, TNFα [ 153 , 154 ].…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…In addition, several genes and pathways are crucial for spermatogenesis [23][24][25][26][27], including the transforming growth factor-β/Smad (TGFβ/Smad) [28], AMP-activated protein kinase (AMPK) [26,29], and mitogen-activated protein kinase (MAPK) signaling pathways [30,31]. During embryonic development, embryogenesis, and adulthood, the TGF signaling pathway regulates a variety of biological activities, including cell proliferation, differentiation, and apoptosis [32].…”
Section: Introductionmentioning
confidence: 99%